Achievements and shortcomings of the implementation of B-learning methodology in the Foreign Language Department at the University of El Salvador, in English Composition courses during the second semester of the year 2013. - Martínez Agreda, Josué Isaí
Technology has been a very important role in education, many techniques has been developed to support learning process. One of the methodologies that has been used in last years is b-learning, which is a form of education that combines face-to-face classroom methods with computer-mediated activities. B-learning proposes an alternative for innumerable people that for some reason are no able to assist face to face classes in universities or schools regularly. In the Foreign Language Department of the University of El Salvador, this method would not only be the solution for the students that cannot attend traditional classes every day, but this could be the answer to solve the overpopulation, a problem which the department deal with, since this is one of the biggest departments of the whole University of El Salvador and one of the biggest issues is the quantity of students, which create the little room for students, insufficient teaching stuff and overcrowded courses. This research is oriented to describe characteristic and advantages of b-learning methodology implementation in the Foreign Language Department at the University of El Salvador documenting the process of application as well as its benefits and shortcomings using this methodology to inform to all the protagonists, the research provides results that can help as a backup for future development of a full electronic distance methodology in the department.